2013
DOI: 10.1002/eji.201243100
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus‐specific T cells are detectable in early childhood and allow assignment of the infection status in children with passive maternal antibodies

Abstract: Serological identification of the cytomegalovirus (CMV) status in children less than 18 months of age is complicated by the variable persistence of maternal antibodies. As T cells are not passively transferred, we attempted to assess whether CMV-specific cellular immunity may be superior to determine the actual CMV status; we also performed a functional characterization of T-cell immunity in childhood. Antibodies from 59 mothers and 168 children were determined, and specific CD4 + T cells were identified by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
2
18
0
2
Order By: Relevance
“…At 24 weeks, Ͻ20% of infants had IgG of high avidity, which could represent either transplacentally acquired maternal antibody or already mature infant antibody from primary infection. Our results indicate that most maternal antibody has waned by 6 months, consistent with a study from China suggesting that the maternally acquired anti-CMV IgG in infants disappears before 8 months of age (24); similarly, a study from Germany concluded that maternal antibody against CMV decayed by 12 months (25).…”
Section: Discussionsupporting
confidence: 91%
“…At 24 weeks, Ͻ20% of infants had IgG of high avidity, which could represent either transplacentally acquired maternal antibody or already mature infant antibody from primary infection. Our results indicate that most maternal antibody has waned by 6 months, consistent with a study from China suggesting that the maternally acquired anti-CMV IgG in infants disappears before 8 months of age (24); similarly, a study from Germany concluded that maternal antibody against CMV decayed by 12 months (25).…”
Section: Discussionsupporting
confidence: 91%
“…Several methods rely on the functional analysis of T-cell-secreted cytokines or the T-cell phenotype (i.e., gamma interferon [IFN-␥], tumor necrosis factor alpha [TNF-␣], interleukin 2 [IL-2], CD107a, programmed cell death protein 1 [PD-1]) upon antigen stimulation, while other methods, such as tetramer assays, are based on the direct detection of antigen-specific T cells or cell proliferation assays (14)(15)(16)(17). Moreover, tetramer assays are limited to a few human leukocyte antigen (HLA) haplotypes and thus may not be applicable for all patients.…”
mentioning
confidence: 99%
“…In this study, we have performed a detailed comparative analysis of the performance characteristics of three assay principles for the detection of cellular immunity toward CMV and M. tuberculosis in samples from deceased donors. Unlike latent infection with M. tuberculosis, where the assignment of the infection status is hampered by the lack of an independent gold standard for positivity, evaluation of CMV-specific T cell assays has the advantage that CMV-IgG serology may serve as a reliable gold standard for the true infection status (6,7,13) and was therefore included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with humoral IgG as a gold standard for CMV infection, the presence of CMV-specific immunity was shown to closely correlate with antibody responses (6,7). Likewise, specific immunity toward M. tuberculosis is readily detectable in vitro.…”
Section: Introductionmentioning
confidence: 99%